Using Composted Poultry Manure (Litter) in Mulched Vegetable Production - George Hochmuth; Robert Hochmuth; Rao Mylavarapu (EDIS)
SL-293, a 9-page illustrated fact sheet by George Hochmuth, Robert Hochmuth, and Rao Mylavarapu, answers vegetable producers’ questions about what poultry manure and litter are, what plant nutrients they contain, considerations for using them, results of research in Florida, how to use it in a mulched-bed system, and how to collect and submit for testing poultry manure samples. Includes references. Published by the UF Department of Soil and Water Science, October 2009.